LITERATURE OF REVIEW THE INFLUENCE OF PRODUCT VARIATION, PROMOTION INTENSITY, AND CUSTOMER TRUST ON CUSTOMER PURCHASE DECISIONS ON HISANA FRIED CHICKEN SALES IN BEKASI - Andreas Kristhianto (Draf Solusi Indonesia, 2023)
This research is a literature review that examines theinfluence of product variation, promotion intensity,and customer trust on customer purchase decisions.This research was conducted at Hisana Fried ChickenSales in Bekasi City. This research uses quantitativemethods with an unknown population so theminimum sample used is the approach from Heir et alwith a sample size of 85 respondents